Challenges in Dengue Vaccines Development: Pre-existing Infections and Cross-Reactivity - Izmirly, Abdullah M.; Alturki, Sana O.; Alturki, Sawsan O.; Connors, Jennifer; Haddad, Elias K. (Frontiers in Immunology, 2020)
Dengue is one of the most frequently transmitted mosquito-borne diseases in the world, which creates a significant public health concern globally, especially in tropical and subtropical countries. It is estimated that more than 390 million people are infected with dengue virus each year and around 96 million develop clinical pathologies. Dengue infections are not only a health problem but also a substantial economic burden. To date, there are no effective antiviral therapies and there is only one licensed dengue vaccine that only demonstrated protection in the seropositive (Immune), naturally infected with dengue, but not dengue seronegative (Naïve) vaccinees. In this review, we address several immune components and their interplay with the dengue virus. Additionally, we summarize the literature pertaining to current dengue vaccine development and advances. Moreover, we review some of the factors affecting vaccine responses, such as the pre-vaccination environment, and provide an overview of the significant challenges that face the development of an efficient/protective dengue vaccine including the presence of multiple serotypes, antibody-dependent enhancement (ADE) as well as cross-reactivity with other flaviviruses. Finally, we discuss targeting T follicular helper cells (Tfh), a significant cell population that is essential for the production of high-affinity antibodies, which might be one of the elements needed to be specifically targeted to enhance vaccine precision to dengue regardless of dengue serostatus.